2023
DOI: 10.21203/rs.3.rs-2454479/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk of dengue, Zika, and chikungunya transmission in the metropolitan area of Cucuta, Colombia: cross-sectional analysis, baseline for a cluster-randomised controlled trial of a novel vector tool for water containers

Abstract: Background Arbovirus diseases such as dengue, Zika, and chikungunya are a public health threat in tropical and subtropical areas. In the absence of a vaccine or specific treatment, vector management (in this case the control of the primary vector Aedes aegypti) is the best practice to prevent the three diseases. A good understanding of vector behaviour, ecology, human mobility and water use can help design effective vector control programmes. This study collected baseline information on these factors for iden… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Although many studies affirm that women are at a higher risk for arbovirus infection, since they spend longer periods at home, considering the domestic habits of the Aedes aegypti vector 32 , 33 , this study demonstrated a higher prevalence of previous infections with the DENV in men (p < 0.018) ( Table 5 ). This can be justified by the fact that infections did not occur in rural households but in urban areas, with trips to the local towns being mostly undertaken by men and, for cultural reasons, women remaining at home to perform chores and take care of children.…”
Section: Discussionmentioning
confidence: 55%
“…Although many studies affirm that women are at a higher risk for arbovirus infection, since they spend longer periods at home, considering the domestic habits of the Aedes aegypti vector 32 , 33 , this study demonstrated a higher prevalence of previous infections with the DENV in men (p < 0.018) ( Table 5 ). This can be justified by the fact that infections did not occur in rural households but in urban areas, with trips to the local towns being mostly undertaken by men and, for cultural reasons, women remaining at home to perform chores and take care of children.…”
Section: Discussionmentioning
confidence: 55%
“…However, this association was not observed with Pvs25, suggesting that expression of Pvs230 may be associated with exposure to mosquito bites from both Anopheles and Aedes mosquitoes. Previous entomological data from this region indicate that Anopheles and Aedes mosquitoes are prevalent in the area 45,46 . However, a limitation of this study is that the gSG6-P1 and the Nterm34kDa peptides we evaluated as markers of mosquito exposure have not been extensively validated for their correlation with mosquito abundance 47,48,49 , and we did not collect specific mosquito data from the sites in our study which could be used to confirm exposure to these mosquito species.…”
Section: Discussionmentioning
confidence: 83%
“…ZIKV high-risk concentrated in southern areas characterized by crowded living conditions, limited access to safe water, and strained healthcare centers, creating favorable conditions for the rapid ZIKV transmission. Moreover, the rural municipalities in this area frequently experience standing water deposits such as laundry tanks and provisional water containers, facilitating mosquito breeding and hindering effective vector control efforts [36]. Hotspots of DENV were also identified in the northern central region, primarily containing rural municipalities with limited access to public, educational, and health services.…”
Section: Discussionmentioning
confidence: 99%